1997
DOI: 10.1021/ma9617072
|View full text |Cite
|
Sign up to set email alerts
|

SAXS and TEM Studies on Poly(styrene)-block-poly(ethene-co-but-1-ene)-block-poly(styrene) in Bulk and at Various Interfaces

Abstract: SAXS and TEM measurements are employed in order to study the morphology of poly(styrene)-block-poly(ethene-co-but-1-ene)-block-poly(styrene) (SEBS) with 29 wt % styrene (Kraton G1652) in bulk and at interfaces to different polymers. Temperature-dependent SAXS measurements of the SEBS bulk sample reveal that PS cylinders are hexagonally packed in the EB matrix. The lattice constant increases during cooling from 200 to 120 °C from 27.5 to 29.5 nm and simultaneously an increase of the cylinder radius occurs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
69
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 21 publications
15
69
1
Order By: Relevance
“…2a, which reveals dark domain structures embedded in a bright matrix. By comparing the relative sizes of the dark and bright areas, it is evident (1) The morphologies and mechanical properties of 30 : 70 and 70 : 30 SEBS/i-PP blends were studied by TEM [5,22]. This TEM study showed large irregularly formed domains of more than 1 µm in size, together with spherical domains a few hundred nanometers in size, all of which are very similar to those found in Figs.…”
Section: Low-resolution Imagessupporting
confidence: 62%
See 1 more Smart Citation
“…2a, which reveals dark domain structures embedded in a bright matrix. By comparing the relative sizes of the dark and bright areas, it is evident (1) The morphologies and mechanical properties of 30 : 70 and 70 : 30 SEBS/i-PP blends were studied by TEM [5,22]. This TEM study showed large irregularly formed domains of more than 1 µm in size, together with spherical domains a few hundred nanometers in size, all of which are very similar to those found in Figs.…”
Section: Low-resolution Imagessupporting
confidence: 62%
“…Within the i-PP region, lamellae can be clearly seen. The lamellae have a typical diameter of 20 nm and exhibit the cross-hatched structure, as reported by TEM [5,22]. In both height and phase images, the SEBS tri-block copolymer regions are microphase separated, i.e.…”
Section: High-resolution Imagessupporting
confidence: 59%
“…On the basis of the mass densities of polystyrene 34 (1.01 g/cm 3 ) and the SEBS triblock copolymer 23 (0.91 g/cm 3 ) at the upper glass transition temperature of polystyrene (T g ϭ 100°C), we estimate the volume fraction of styrene in the copolymer to be about 0.28. Since a similar SEBS copolymer (Kraton G1652) of lower molecular weight (M n ϭ 87000) and styrene content (29 wt %) is reported 35 to be microphase-ordered (exhibiting hexagonally packed styrenic cylinders in an EB-rich matrix) at the T g of the copolymer, it follows that the copolymer examined here must likewise be ordered, due to its higher N. Assessment of the copolymer morphology is described below.…”
Section: Morphological Characteristicsmentioning
confidence: 95%
“…In addition, with the same material, different morphologies can be observed in response to the application of shear forces, [5,6] type of solvent used, [7,8] solvent evaporation rate, [9] and film thickness. [10] Sulfonated block copolymers are commonly used as proton-conducting membranes [11 -14] (PCM) in protonexchange membrane fuel cells (PEMFC) and direct methanol fuel cells (DMFC). The application of sulfo-nated block copolymers as PCMs is possible due to the introduction of hydrophilic functional groups, i.e.…”
Section: Introductionmentioning
confidence: 99%